Guaranteed Renewable Life Insurance Under Demand Uncertainty - Michael Hoy; Afrasiab Mirza; Asha Sadanand (Center for Economic Studies and ifo Institute (CESifo), 2018)
Guaranteed renewability is a prominent feature in many health and life insurance markets. It is well established in the literature that, when there is (only) risk type uncertainty, the optimal GR contract with renewal price set at the actuarially fair price for low risk types provides full insurance against reclassification risk. We develop a model that includes unpredictable (and unobservable) fluctuations in demand for life insurance as well as changes in risk type (observable) over individuals' lifetimes. The presence of demand type heterogeneity leads to the possibility that optimal GR contracts may have a renewal price that is either above or below the actuarially fair price of the lowest risk type in the population. Individuals whose type turns out to be high risk but low demand renew more of their GR insurance than is efficient due to the attractive renewal price. This results in incomplete insurance against re-classification risk. Although a first best efficient contract is not possible in the presence of demand type heterogeneity, the presence of GR contracts nonetheless improves welfare relative to an environment with only spot markets. Our results also apply to a comparison of environments with short versus long term (front loaded) insurance contracts.
Keywords: D80; D86; G22; 330; insurance; guaranteed renewability; re-classification risk; demand uncertainty